P1-S2.23 Transgender persons in Guatemala - over-exposed and under-protected - the findings of an RDS behavioural survey. (10th July 2011) - Miller, W; Alvarez, B; Boyce, S; Alvarado, A; Barrington, C; Paz-Bailey, G
Abstract : Background: Male-to-female transgender persons experience the highest HIV prevalence rates of any high risk population in Central America. The purpose of this study is to compare HIV-related risk behaviours, knowledge and exposure to prevention activities among transgender persons and other men who have sex with men (MSM) in Guatemala City. Methods: From September—to December 2010, we conducted a probability-based survey of MSM, including male-to-female transgender persons who have sex with men, using respondent-driven sampling (RDS) in Guatemala City. Data on sexual and drug use behaviour, knowledge of HIV, attitudes, stigma, access to prevention, care, and treatment services were collected by interviewers using Personal Digital Assistants (PDA). Population proportions and 95% CIs, adjusted for RDS sampling weights, were calculated using the Respondent Driven Sampling Analysis Tool (version 6.0). Crude summary statistics were calculated in SAS (version 9.1). Results: A total of 509 MSM, including 99 male-to-female transgender persons enrolled in the study. The mean age for transgendered persons was 29.1 vs 28.0 for non-transgender MSM. Education level and socio-economic status were comparable between the two groups. Transgender persons, in comparison to non-transgender MSM, had higher rates of transactional sex (77.6% vs 41.9% in the past year, respectively), drug use (26.7% vs 3.3% cocaine use in the past month) and prior HIV testing (95.7% vs 68.9%, during lifetime). On the other hand, transgender persons have similar levels of forced sex (14.1% vs 6.5% in the past year), exposure to HIV educational activities (74.2% to 67.8% in the past year), access to free condoms (83.9% to 79.6%) and correct knowledge of HIV prevention (54.8% vs 41.7%) see Abstract P1-S2.23 Figure 1 . Conclusions—Compared to other MSM, transgender persons in Guatemala City more often receive money for sex and use cocaine and are at disproportionately higher risk for HIV infection. While prevention activities, such as HIV testing, seem to be reaching transgender persons, exposure may not translate into increased protection. Findings emphasise the need for innovative HIV prevention activities to address the many facets and levels of vulnerability and social marginalisation experienced by transgender persons in Guatemala City. Such efforts should extend beyond individual-level outreach and information provision to rigorously evaluated intervention strategies at the social and structural levels.